A Comparison of Sharia Screening and Environmental, Social, and Governance Investing in Halal Investment Planning for the Muslim Generation - achmad nasrulloh; Nungki Hayukusuma; Siti Faridah; Agus Eko Sujianto; Amalia Nuril Hidayati (Institute of Research and Community Service at Islamic University of Bunga Bangsa Cirebon, 2026)
The rapid growth of the Islamic capital market—dominated by young Muslims—has given rise to dual investment preferences: absolute adherence to Sharia principles and compliance with Environmental, Social, and Governance (ESG) standards. The integration of these two frameworks often creates ethical dilemmas due to their differing philosophical foundations. This study aims to critically compare Sharia screening mechanisms with ESG standards and to formulate adaptive halal financial planning strategies. Using a systematic literature review method, a qualitative analysis was conducted on OJK regulations, DSN-MUI fatwas, and global sustainability literature. The synthesis confirms strong convergence regarding the rejection of “sin stocks” and the need for increased transparency in corporate governance. Fundamental divergence, however, arises regarding the tolerance threshold for usurious debt systems, where ESG standards could potentially approve environmentally friendly projects that involve usury—which is absolutely prohibited under Islamic commercial law (fiqh muamalah). These findings recommend the need for retail investors to implement dual screening (Sharia-ESG integration). As a strategic projection, stock exchange authorities need to immediately develop a single hybrid index to create an investment architecture that is financially profitable, resilient during crises, and consistent with the essence of Maqashid al-Shariah.